Euplectrus furnius parasitizing Spodoptera frugiperda in maize in Brazil - Vinícius Soares Sturza (Ciência Rural, 2013)
Brazil is among the world’s biggest maize producers and fall armyworm, Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae), is the main insect pest on this crop in the country. Despite the importance of its natural enemies, there still is a lack of information about parasitoids species that attack this insect-pest, such as larval parasitoids. This research reports Euplectrus furnius Walker (Hymenoptera: Eulophidae) parasitizing S. fugiperda larvae on maize crop in Brazil.